2020
DOI: 10.1186/s12887-020-02434-w
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia prevalence and determinants in under 5 years children: findings of a cross-sectional population-based study in Sudan

Abstract: Background Early childhood is an age at risk of anaemia and its deleterious consequences. In Sudan, there is limited evidence on the prevalence and determinant of anaemia in under-five children. This study was conducted in Sudan to assess the prevalence of anaemia in children and to identify its determinants. Methods We conducted a household survey involving children aged 6 months to 5 years in November 2016. A representative population was sampled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…In such a low level of malaria transmission chronic malaria and repeated malaria infections are less common and therefore, may not be a major cause of anaemia. Studies from low to moderate transmission settings, including from Sudan [ 34 ], showed that anaemia was associated with malaria infection but not with the level of malaria transmission [ 27 , 58 60 ]. Moderate-to-severe anaemia (haemoglobin < 80 g/L) is a more sensitive measure to the association between anaemia and malaria compared to anaemia (haemoglobin < 110 g/L), which was used in this study [ 20 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a low level of malaria transmission chronic malaria and repeated malaria infections are less common and therefore, may not be a major cause of anaemia. Studies from low to moderate transmission settings, including from Sudan [ 34 ], showed that anaemia was associated with malaria infection but not with the level of malaria transmission [ 27 , 58 60 ]. Moderate-to-severe anaemia (haemoglobin < 80 g/L) is a more sensitive measure to the association between anaemia and malaria compared to anaemia (haemoglobin < 110 g/L), which was used in this study [ 20 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within each household, all household members were included in the study. Individual and household-related data were collected using a coded pre-tested questionnaire [ 34 ] and capillary blood samples were obtained from all eligible individuals. Written informed consent was obtained from participants.…”
Section: Methodsmentioning
confidence: 99%
“…Within each household, all household members were included in the study. Individual and household-related data were collected using a coded pre-tested questionnaire [122] and capillary blood samples were obtained from all eligible individuals. Written informed consent was obtained from participants.…”
Section: Methodsmentioning
confidence: 99%
“…In such a low level of malaria transmission chronic malaria and repeated malaria infections are less common and therefore, may not be a major cause of anaemia. Studies from low to moderate transmission settings, including from Sudan [122], showed that anaemia was associated with malaria infection but not with the level of malaria transmission [119,[144][145][146]. Moderate-to-severe anaemia (haemoglobin < 80g/L) is a more sensitive measure to the association between anaemia and malaria compared to anaemia (haemoglobin < 110g/L), which was used in this study [59,61].…”
Section: Estimates Of Two-level Logistic Regression Models For the As...mentioning
confidence: 99%
See 1 more Smart Citation